BRIDGING THE GAP. Issue 3 (12th March 2014) - Hulstijn, Jan H.; Young, Richard F.; Ortega, Lourdes; Bigelow, Martha; DeKeyser, Robert; Ellis, Nick C.; Lantolf, James P.; Mackey, Alison; Talmy, Steven
<x content-type="archive" xml:space="preserve">Abstract</x> For some, research in learning and teaching of a second language (L2) runs the risk of disintegrating into irreconcilable approaches to L2 learning and use. On the one side, we find researchers investigating linguistic-cognitive issues, often using quantitative research methods including inferential statistics; on the other side, we find researchers working on the basis of sociocultural or sociocognitive views, often using qualitative research methods including case studies and ethnography. Is there a gap in research in L2 learning and teaching? The present article developed from an invited colloquium at the 2013 meeting of the American Association for Applied Linguistics in Dallas, Texas. It comprises nine single-authored pieces, with an introduction and a conclusion by the coeditors. Our overarching goals are (a) to raise awareness of the limitations of addressing only the cognitive or only the social in research on L2 learning and teaching and (b) to explore ways of bridging and/or productively appreciating the cognitive-social gap in research. Collectively, the nine contributions advance the possibility that the approaches are not irreconcilable and that, in fact, cognitive researchers and social researchers will benefit by acknowledging insights and methods from one another.